1-{(E)-[4-Bromo-2-(trifluoromethoxy)phenyl]iminomethyl}naphthalen-2-ol - Kargili, Hakan; Macit, Mustafa; Alpaslan, Gokhan; Buyukgungor, Orhan; Erdonmez, Ahmet (Int Union Crystallography, 2013)
The title compound, C18H11BrF3NO2, crystallizes in the phenol-imine tautomeric form, with a strong intramolecular O-H center dot center dot center dot N hydrogen bond. The dihedral angle between the naphthalene ring system and the benzene ring is 28.54 (10)degrees.
Macit, Mustafa/0000-0002-5672-5161